(RETRACTED) THE ACTUALIZATION LITERATURE BASED LEARNING VERBAL-LINGUISTIC INTELLIGENCE - Halil, Nur Ihsan (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
Retraction Notice Leksika, Vol.11, No.1, February 2017 Purwokerto, January 13, 2021 First Published Feb, 2017 Article Information Original Article: http://jurnalnasional.ump.ac.id/index.php/LEKSIKA/article/view/7374 Abstract At the request of the Author, the following article has been retracted: Halil, N. Ihsan. 2017. The actualization literature based learning verbal-linguistic intelligence. Leksika Vol. 11, No.2, February 2017. Purwokerto: Faculty of Letters, Universitas Muhammadiyah Purwokerto. Due to some lack of coordination with the corresponding author, the article had been managed to have a double publication. On behalf of Leksika, I send my deep apology to the author and our readers. Thank you, Best regards, Khristianto Editor-in-Chief Leksika: Jurnal bahasa , sastra dan pengajarannya.